2014
DOI: 10.7567/jjap.53.09pb07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NiO addition on (K,Na,Li)NbO3–BaZrO3–(Bi,Na)TiO3-based ceramics

Abstract: The effects of CuO or NiO addition on the sintering temperature and electrical properties of 0.92(K 0.47 Na 0.47 Li 0.06 )NbO 3 -0.07BaZrO 3 -0.01 (Bi 0.5 Na 0.5 )TiO 3 ceramics with a temperature-stable morphotropic phase boundary were investigated. The ceramics without any additives and those with NiO exhibited a tetragonal phase. The ceramics with CuO exhibited the coexisting orthorhombic and tetragonal phases. The sintering temperature was reduced by the addition of NiO or CuO. NiO addition was also effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…e presence of nucleating agents, such as TiO 2 and various oxides, in the glassceramic composition favors nucleation and crystal growth. Since the surface tension decreases, the nucleation rate increases in the vitreous system [13,20,21]. e addition of niobium oxide in addition to promoting crystallization also enables the formation of crystals of the perovskite group.…”
Section: Introductionmentioning
confidence: 99%
“…e presence of nucleating agents, such as TiO 2 and various oxides, in the glassceramic composition favors nucleation and crystal growth. Since the surface tension decreases, the nucleation rate increases in the vitreous system [13,20,21]. e addition of niobium oxide in addition to promoting crystallization also enables the formation of crystals of the perovskite group.…”
Section: Introductionmentioning
confidence: 99%
“…The Pb-based materials have been used in many applications such as actuators and sensors. [1][2][3] Possible replacements for Pb-based materials are (Bi,Na)TiO 3 , [4][5][6][7][8][9][10][11] (K,Na)NbO 3 , [12][13][14][15] and BaTiO 3 [16][17][18] and their solid solutions. Among them, (1-x)(Bi,Na)TiO 3 -xBaTiO 3 (BNT-100xBT) and related materials have been studied intensively because of their excellent electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Nakai et al who were members of our research group, revealed that (Na 0.50 K 0.45 Li 0.05 )NbO 3 (NKLN) solid solutions produced by the malic acid complex solution method (MACSM) were soft materials exhibiting excellent piezoelectric properties, with a d 33 of 151 pC/N, a k p of 32% and a radial-mode mechanical quality factor Q m (p) of 87, and a high T c of 462C [7]. Meanwhile Ba(Zr 0.2 Ti 0.8 )O 3 x(Ba 0.7 Ca 0.3 )TiO 3 (BZTxBCT) solid solutions with the same crystal structure as NKLN have attracted much attention due to their good piezoelectric properties at the tricritical point of the morphotropic phase boundary (MPB) between the rhombohedral (R) and tetragonal (T) phases [8][9][10][11][12]. In particular, although the operating temperature range for (Ba 0.85 Ca 0.15 )(Zr 0.1 Ti 0.9 )O 3 (BCZT, x = 0.5) is limited to near room temperature owing to its comparatively low T c of 8594C, it exhibits good piezoelectric properties with d 33 = 545650 pC/N, k p = 5357, k 33 = 65%, and Q m = 125, which are comparable to those for soft PZT at room temperature [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile Ba(Zr 0.2 Ti 0.8 )O 3 x(Ba 0.7 Ca 0.3 )TiO 3 (BZTxBCT) solid solutions with the same crystal structure as NKLN have attracted much attention due to their good piezoelectric properties at the tricritical point of the morphotropic phase boundary (MPB) between the rhombohedral (R) and tetragonal (T) phases [8][9][10][11][12]. In particular, although the operating temperature range for (Ba 0.85 Ca 0.15 )(Zr 0.1 Ti 0.9 )O 3 (BCZT, x = 0.5) is limited to near room temperature owing to its comparatively low T c of 8594C, it exhibits good piezoelectric properties with d 33 = 545650 pC/N, k p = 5357, k 33 = 65%, and Q m = 125, which are comparable to those for soft PZT at room temperature [9][10][11][12]. Thus, BCZT is likely to be applied as an end member in solid solutions containing other lead-free piezoelectric materials with a high T c , rather than being directly used for piezoelectric applications.…”
Section: Introductionmentioning
confidence: 99%